Death in the afternoon - Hemingway, Ernest, 1899-1961 (Scribner, 2003)
Hemingway's Classic Portrait Of The Pageantry Of Bullfighting. Still considered one of the best books ever written about bullfighting, Death in the Afternoon reflects Hemingway's belief that bullfighting was more than mere sport. Here he describes and explains the technical aspects of this dangerous ritual, and "the emotional and spiritual intensity and pure classic beauty that can be produced by a man, an animal, and a piece of scarlet serge draped on a stick." Seen through his eyes, bullfighting becomes an art, a richly choreographed ballet, with performers who range from awkward amateurs to masters of great grace and cunning. A fascinating look at the history and grandeur of bullfighting, Death in the Afternoon is also a deeper contemplation on the nature of cowardice and bravery, sport and tragedy, and is enlivened throughout by Hemingway's pungent commentary on life and literature. Hemingway's Classic Portrait Of The Pageantry Of Bullfighting. Still considered one of the best books ever written about bullfighting, "Death in the Afternoon" reflects Hemingway's belief that bullfighting was more than mere sport. Here he describes and explains the technical aspects of this dangerous ritual, and "the emotional and spiritual intensity and pure classic beauty that can be produced by a man, an animal, and a piece of scarlet serge draped on a stick." Seen through his eyes, bullfighting becomes an art, a richly choreographed ballet, with performers who range from awkward amateurs to masters of great grace and cunning. A fascinating look at the history and grandeur of bullfighting, "Death in the Afternoon" is also a deeper contemplation on the nature of cowardice and bravery, sport and tragedy, and is enlivened throughout by Hemingway's pungent commentary on life and literature.